The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1055/s-2007-1021022
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Adaptation and Weight Fluctuation in College Wrestlers

Abstract: Myocardial adaptation and weight fluctuation of seven college wrestlers was examined during a competitive season. Standard M-mode measurements were used to determine left ventricular (LV) end diastolic and end systolic dimensions, fractional shortening, LV diastolic posterior wall thickness (DPW), diastolic interventricular septal thickness (DIVS), and LV mass (LVM) during preseason (test 1) and four months later at the season's end (test 2). The wrestlers' qualifying weights ranged from 53.6 to 80.5 kg and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several other factors, individual to the patient, such as changes in wall motion and thickness, intramyocardial and transmyocardial conduction abnormalities, and cancelling effects on electrical activity are presumably involved and may explain why ischaemia is associated with differing directional changes in R wave amplitude. Shusterman et al (2007) also stated that the changes in the QRS amplitude might be caused by the development of myocardial ischaemia, changes in body position, or a combination of these factors. For example, an ischaemiainduced chest pain could have led to the changes in body position, which in turn could generate the high-frequency muscle and movement artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other factors, individual to the patient, such as changes in wall motion and thickness, intramyocardial and transmyocardial conduction abnormalities, and cancelling effects on electrical activity are presumably involved and may explain why ischaemia is associated with differing directional changes in R wave amplitude. Shusterman et al (2007) also stated that the changes in the QRS amplitude might be caused by the development of myocardial ischaemia, changes in body position, or a combination of these factors. For example, an ischaemiainduced chest pain could have led to the changes in body position, which in turn could generate the high-frequency muscle and movement artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although this was reported previously in renal patients after dehydration as a result of multiple haemodialysis sessions (Drighil et al, 2008; Madias & Narayan, 2003) and in patients with peripheral oedema after its amelioration followed by the use of diuresis (Madias, 2006b), to our knowledge this is the first study to investigate the effects of dehydration and rehydration on the sums of amplitude of the P waves (ΣP) and QRS complexes (ΣQRS) in 12‐lead ECG and LVESV, LVEDV, and stroke volume of Greco‐Roman wrestlers. Smith et al (1994) reported that resting left ventricular cavity size and contractility, as demonstrated by the consistency of LVED, LVES, and fractional shortening, does not change during a competitive wrestling season accompanying a 7.5±1.5% mean weight fluctuation (range 4.4–9.1%). Consistent with Smith and colleagues (1994), results of the present investigation revealed that LVESV, LVEDV, and stroke volume were reduced after a 3–4% weight loss through dehydration, all of which returned to baseline values after rehydration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations